TECHNICAL EDUCATION AS A PLATFORM FOR VISUAL ART EDUCATION - DOVALOVA, Dana (Trends in education, 2012)
The EU recommendations on basic skills, that one should get in her/his education, involve also technical skills. In this context, it was supposed that the new Education Act will strengthen the position of technical education in the education system at primary schools, to improve vocational training of youth and increase the number of students studying in technical fields. In reality such strengthening of technical education did not find support in the state educational program for education level ISCED 2 and the status of technical education in primary schools has been weakened. Technical education is only part of the study in vocational schools with technical orientation, but it has its unique position also in visual art education. Technical skills along with a talent create a basis for the study of visual art disciplines, what is another reason to strengthen technical education at primary schools.
Keywords: technical education; visual art education; technical skills; national/school education program.